Creativity in organisations - Random Publications LLP
It is granted that creativity and innovation are critical to growth and performance of an organization. The intuitive conception of creativity holds that it involves the production of new ideas. Creativity is not simply a matter of idea production —although this may be an important influence on creativity. Rather, creativity is defined as production of high quality, original, and elegant solutions to problems. To capitalize on creativity and innovation, organizations must bear in mind three key considerations. Creativity has been recognized as a key component of a firm's ability to adapt to a rapidly changing competitive landscape. However, what role does creativity play in the adaptation process? Two sets of theories attempt to address this question: contingency theory and strategic choice theory. Creativity indeed plays a crucial role in organizations at all levels. Following same old techniques might not yield results everytime. Remember, change is inevitable. You just can't stick to what was taught in your school or college. Creativity is reaching to innovative solutions, new ideas, unique concepts through brainstorming, discussion amd healthy communication among employees. Organizations that use a traditional hierarchical structure rely on a vertical chain-of-command as the prime method of organizing employees and their responsibilities. Military, government, and other very-large organizations use a hierarchy to determine the level of control employees have over theft work as well as their rank relative to others. In order for a firm to remain relevant in the pursuit of its mission, its managers must pay attention to both parts of this process, supporting the generation of creative ideas as well as the realization of the potential value of those ideas through the innovation process. In this book we focus on the first of these priorities, namely, organizational creativity. Contents: 1. Introduction, 2. Organizing, 3. Leadership and Organizational Management, 4. Organizational Control Techniques, 5. Creative Marketing Methods, 6. Business Plan for an Established Business, 7. Entrepreneurial Qualities, 8 Genesis of Organisational Behaviour, 9. Organizational Theory and Structures, 10. Employee Performance Management in Organisations, 11. The Affective Revolution.